Knowledge-based education and the management of artificial intelligence tools: Experiences and good practices - Darío Cárdenas Espinosa, Rubén; César Caicedo Eraso, Julio; Jiménez Pitre, Iris (Edelweiss Applied Science and Technology, 2024)
The purpose of the research is to share experiences of good practices in the implementation of Knowledge-Based Education (CBE) and the management of Artificial Intelligence (AI) tools in the classroom. The methodology corresponds to a documentary research with a qualitative approach. A systematic review of the literature and analysis of successful cases in higher education programs were carried out. Key factors for the success of CBE and AI in the classroom were identified. The result obtained was the elaboration of a set of recommendations for the implementation of CBE and AI in the classroom that can serve as a guide to integrate AI tools into their teaching practice. It was concluded that CBE and AI are powerful tools that contribute to improving student learning, as long as ethical considerations and relevant validation strategies are taken into account, however, their implementation in the classroom is subject to proper planning by the counselor and the responsible use of technological tools. The implementation of AI tools is a means to improve the quality of education and not an end.